Jogos digitais na reabilitação cognitiva: aplicação limitações e aplicabilidade. - Aires, Árthemys Mired Campos Confessor (2023)
Information and Communication Technologies (ICT) have triggered significant changes in various aspects of society, including the economy, culture, and social interactions. For example, the internet has introduced new paradigms of communication and sociability, evolving from an everyday technological revolution into a tecnoexistential revolution that has profoundly shaped people's experiences, perspectives, and understandings. As digital technologies continue to develop, the way people connect with themselves and others also undergoes significant transformations, impacting their subjectivity. These technological transformations bring with them numerous possibilities, including in the field of mental health. One of these possibilities is the use of digital games as tools in psychotherapeutic practice, expanding traditional horizons of intervention. In this context, a genuine interest arises in understanding the potential of digital games in the field of psychotherapy, especially concerning their positive impact on individuals' cognitive functions. With this purpose in mind, this research aims to explore the applications, modalities, and limitations of using digital games in cognitive rehabilitation. To achieve this objective, a comprehensive literature review on electronic games was conducted, presenting statistical data and examples of game categories. Subsequently, various ways in which these games can be applied in psychotherapeutic clinics and cognitive rehabilitation were discussed, highlighting their ability to improve executive functions and assist in the rehabilitation of cognitive deficits. Furthermore, a comprehensive scope review of national and international scientific production related to the use of electronic games in cognitive rehabilitation processes was carried out. This review involved the analysis of studies that explored the impact of electronic games on different disorders and pathologies, ranging from Attention Deficit Hyperactivity Disorder (ADHD) to Post-Traumatic Stress Disorder (PTSD). The results of this review challenge the perception that electronic games are merely forms of entertainment, emphasizing their applicability in various fields of knowledge. They prove valuable as educational tools, providing an interactive and playful approach to acquiring new knowledge. Additionally, in the field of healthcare, they contribute to improving the quality of life for patients with chronic diseases or mental disorders. Therefore, the use of Information and Communication Technologies, specifically video games, emerges as an effective and viable alternative in the context of mental health promotion and prevention. Through their audiovisual elements, these tools enable the creation of multisensory environments, enriching the patient's experience and making it more engaging. When an individual engages in a digital game, they are challenged to analyze events, solve problems, and make decisions, which proves beneficial for stimulating cognitive functions and promoting the development of socioemotional skills.